Evaluation of prevalence, clinical presentation and risk factors of coronary slow flow phenomenon: a single-center study - Patil, Shaileshkumar; Sarkar, Achyut; Patil, Manisha; Ahmed, Imran; Pande, Arindam (International Journal of Research in Medical Sciences, 2021)
Background: The coronary slow flow phenomenon has been revealed to be associated with life-threatening arrhythmias and sudden cardiac death. Currently, clinical features and risk factors of patients with the coronary slow flow phenomenon are incompletely understood. The present study aimed to evaluate the prevalence, clinical presentation, risk factors and evidence of ischemia in patients with coronary slow flow. Methods: This observational study was conducted at a tertiary-care center in India between February 2013 and August 2014. A total of 60 consecutive patients whose coronary angiogram revealed coronary slow flow were included in the study. According to the number of blood vessels involved, patients were divided into group-1 (29 patients with single-vessel disease), group-2 (22 patients with double-vessel disease), and group-3 (9 patients with triple-vessel disease). Clinical presentation and risk factors were compared among groups. Results: Prevalence of coronary slow flow was 2.97% with greater prevalence amongst male patients (p=0.030). Unstable angina was the most common presentation (p=0.030). Among the traditional risk factors, there was a significantly higher prevalence of smoking (p=0.036), family history of coronary artery disease (p=0.049) and dyslipidemia (p=0.045) in group-3 patients compared to other groups. Among all groups, triglycerides (p=0.020), low-density lipoprotein cholesterol (p=0.046), highly sensitive C-reactive protein (p=0.007) levels, homocysteine (p=0.481), and patterns of ECG abnormalities were significantly different between the three groups. In addition, mean frame counts with coronary slow flow phenomenon in left anterior descending artery (p<0.001), left circumflex artery (p<0.001) and right coronary artery (p=0.005) increased significantly with increase in number of vessels involved. Conclusions: Coronary slow flow was relatively common among patients who presented with unstable angina. Male sex, smoking, and dyslipidemia can be considered as independent risk factors for this phenomenon.